Frequency of Anemia/IDA and Associated Risk Factors Among Working Women of a Medical Center in Tehran, Iran: A Cross-Sectional Study - Giti Noghabaei; Maliheh Arab; Sara Payami; Behnaz Ghavami; Behnaz Nouri; Roya Parkhideh (Wolters Kluwer Medknow Publications, 2024)
Introduction: The study aimed to examine anemia prevalence and risk factors in employed women at a medical center compared to unemployed women from a charity center, with anemia defined as hemoglobin <120 g/L and iron deficiency as serum ferritin <30 ng/mL or serum iron <10 mcg/dL. Material and Methods: This cross-sectional study included 651 employed, non-pregnant randomly selected women aged 20-67 years. Participants completed questionnaires on sociodemographic, nutritional, and obstetrical characteristics. Blood indicators such as hemoglobin, serum ferritin, iron, and TIBC were measured. Results: Out of 651 participants, 395 (60.7%) had anemia/IDA (Hb <120 g/L, ferritin <30 ng/mL, or iron <10mcg/dL), comprising 308 (47.3%) having IDA and 215 (33%) having anemia. Younger age (<40 years) and menorrhagia were individually associated with 1.84- and 2.79- times increased risk of developing anemia in the studied population, respectively. A higher number of shifts and lack of vegetable consumption were found to be significantly prevalent in the anemic group. The prevalence of anemia/IDA among hospital staff and referred women was 60.7% and 43.1%, respectively. Conclusions: The study emphasized the influence of employment on the prevalence of anemia/IDA among hospital staff compared to unemployed women.